The Pesticide Effect of Sucrose Fatty Acid Esters on Calacarus heveae Feres (Acari: Eriophyidae) in two rubber tree clones - Daud, Rodrigo Damasco; Feres, Reinaldo José Fazzio; Boscolo, Maurício (BioAssay, 2012)
Sucrose esters are biodegradable, non pollutant and health safe; moreover, they have shown great potential in the pest control. We tested a crude mix of sucrose esters on the survivorship and oviposition of Calacarus heveae Feres (Acari, Eriophyidae) females, an important rubber tree pest mite, from leaflets of clones GT 1 and RRIM 600. The mites were kept on stock arenas placed in rearing chamber at 28 + 0,1C°, 80 + 10% of relative humidity and 12h of light phase about two weeks before the essays. The essay arenas were made from cut leaflets on wet cotton layer, into Petri dishes (n = 11). The mites were transferred to essay arenas made with leaflets from the same clone of stock arenas. The survivorship of females sprayed with sucrose esters in the concentrations of 1, 2, 3 and 4 g/L and their oviposition effect with 0.5 and 1g/L were analyzed. The mites sprayed with 4 g/L had about 80% of mortality, while those with 1 g/L around 60%. All mites that died in the treatments with sucrose ester became dark with wrinkled tegument and decreased their body volume, suggesting dehydration. We also observed the efficacy of 1g/L concentration to decrease the female oviposition in about 50%, in the third day after spraying. No differences were observed in the mortality and oviposition between females kept on both clones.